TANGGAPAN TAMU TERHADAP FASILITAS ATRIBUT DI GRAND ELITE HOTEL PEKANBARU - ", Sheila; Sidiq, Siti Sofro (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted to find out more about the attribute facilities at Grand Elite Hotel Pekanbaru and to find out guest responses to attribute facilities at Grand Elite Hotel Pekanbaru. The research method used in this study is a quantitative method to examine the problems raised. The sample technique used is a sampling technique based on chance. The samples taken were 50 respondents, who were taken as research respondents were guests who came to the Grand Elite Hotel Pekanbaru with the intention to find out the guests' responses to the available facilities. Data collection was carried out using interviews, observations, and questionnaires. The analysis technique used in this study is descriptive statistics to describe guest responses to facility attributes. Facilities at Grand Elite Hotel Pekanbaru include business services and facilities such as internet connectivity, suites and computers, security facilities such as reconnaissance holes, water spray systems, electronic locks, and surveillance cameras, basic facilities such as mattresses and pillows, quality furniture, and towels, personal services such as express laundry services and bell staff services, free extras such as newspapers, SPA, breakfast, and local telephone calls, dining facilities such as bars & lounges, snack bars, family restaurants, and room service, distinctive rooms Hotels such as work desks, and non-smoking rooms, airport / meeting facilities such as airport transfers, meeting room facilities, and banquet services, advertising and parking such as information boards, directions, and parking lots, fitness facilities such as gymnastics, dressing rooms, and free sauna. The results of the study show that the guest responses to the attribute facilities at Grand Elite Pekanbaru Hotels are in the good category with the highest score located in the dining facilities.Â Keywords: Guest Responses, Facilities, Hotels